Resistencia fenotípica a eritomicina en Staphylococcus spp. aislados de infecciones en - Denamiel, G. (2004)
A total of 98 strains of erythromycin-resistant Staphylococcus spp isolated from otitis and skin infections in dogs from Buenos Aires city and outskirts were tested for their resistance phenotype profile to erythromycin (Eri). Of these, 73.5% (72) of Staphylococcus showed cMLS phenotype, 10.2% (10) showed iMLS phenotype and 16.3% (16) showed M phenotype. Staphylococci with L phenotype were not found. The Eri MIC for all the strains was over 256 µg/ ml. Throughout these studies, we can have more information about the evolution in the epidemiological resistance to erythromycin, and errors in the interpretation of sensibility test could be reduced. \n